Ureteroscopy and Lithotripsy service in Patan Hospital - Shrestha, Samir; Shah, Surendra; Poudyal, Sanjay; Shah, Jay N; Jaiswal, Vijay K (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: With advent of URSL (ureterorenoscopy and lithotripsy) and other minimally invasive technique viz; SWL (shock wave lithotripsy), PCNL (percutaneous nephrolithotomy), the urinary stones management has taken a giant leap to serve mankind. The aim of this study is to review a wide series of ureteral stones in which ureteroscopy combined with endoscopic lithotripsy was chosen as the first approach for the treatment of ureteral calculi and to study its diagnostic efficacy. Methods: This is a retrospective study that was carried out in Patan Hospital from Feburary 2010 to Jan 2013. In all cases preoperatively intravenous urography, and a plain film of the urinary tract was taken before the procedure. The operations were carried out with the patient under general anesthesia. Rigid ureteroscopes and the pneumatic lithotripter were used. The fragments were extracted with forceps or baskets assisted with saline flush. Results: We analyzed the result of URSL done in our hospital for variety of urology problem. We found age group 20-40, being the most common group to develop urinary calculus. Most of our patient had single stone of size >5mm. Upper ureter, mid ureter and distal ureter comprises of 4, 30 and 56 stone respectively. Our success rate of URS insertion is 96%(96/100) with complete stone fragmentation with expulsion of the fragments occurred in 97.8%(88/90). Our major perioperative complication were 3% without mortality. Conclusion: URS is useful for diagnostic purpose & URSL is safe and treatment of choice for mid and lower ureteic calculus